Complementary methods of treatment of alcoholic dependence syndrome (F10.2) in the practice of a family medicine - А. I. Kharkovskaya; W. Zukow; N. Chukhraiev; A. V. Unichenko (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
A program of a multilevel approach to the treatment of alcohol dependence syndrome (F10.2) in the practice of a family medicine physician based on the combined use of psychotherapeutic correction using a cognitive-behavioral approach, detoxification of the body using singlet oxygen therapy and a decrease in the patient's craving for alcohol by the method of transcranial micropolarization is presented. According to the results of treatment, out of 46 patients in the main group, remission over 1 year was observed in 38 patients undergoing treatment.